Optical Coherence Tomography Reveals Longitudinal Changes in Retinal Damage Under Different Treatments for Neuromyelitis Optica Spectrum Disorder - Zeng, Pei; Du, Chen; Zhang, Rui; Jia, Dongmei; Jiang, Feng; Fan, Moli; Zhang, Chao (Frontiers in Neurology, 2021)
Background: Progressive retinal neuroaxonal damage after acute optic neuritis may occur in neuromyelitis optica spectrum disorder (NMOSD). However, it is unclear if treatments used to prevent attacks influence neurodegeneration. Objectives: We aimed to investigate retinal damage in patients treated with disease modifying drugs in a longitudinal study. Methods: We retrospectively included 50 patients with aquaporin 4-antibody-seropositive NMOSD. Peripapillary retinal nerve fiber layer thickness (pRNFL), macular ganglion cell complex (mGCC) thickness, total macular volume (TMV) and optic disc measures were acquired by spectral domain optical coherence tomography in patients treated with tocilizumab, rituximab, and azathioprine. Results: Longitudinally, in eyes with a history of ON (NMOSDON+), we observed annual thinning of mGCC (tocilizumab: -1.77 (-3.44, -0.09) μm, p=0.041; rituximab: -2.03 (-3.58, -0.48) μm, p=0.017; azathioprine: -1.79 (-2.22, -1.37) μm, p<0.001) and pRNFL (tocilizumab: -2.07 (-0.75, -3.39) μm, p=0.005; rituximab: -2.18 (-0.36, -4.00) μm, p=0.023; azathioprine: -2.37 (-0.98, -3.75)μm, p=0.003), reduced TMV (tocilizumab: -0.12 (-0.22, -0.01)mm3,p=0.028; rituximab: -0.15 (-0.21, -0.08)mm3, p=0.001; azathioprine: -0.12 (-0.20, -0.04)mm3, p=0.006) and increased cup area (tocilizumab: 0.08 (-0.01, 0.16) mm2, p=0.010; rituximab: 0.07 (0.01, 0.12) mm2, p=0.019; azathioprine: 0.14 (0.02, 0.26) mm2, p=0.023). However, we detected no significant differences in annual changes in mGCC, pRNFL, TMV, and cup area between patients with tocilizumab, rituximab, and azathioprine in NMOSDON+ eyes. NMOSDON- eyes did not display mGCC or pRNFL thinning in patients treated with tocilizumab and rituximab. Intriguingly, we observed significant thinning of mGCC in patients treated with azathioprine compared with tocilizumab (-0.84 (-1.50, -0.18) μm vs -0.19 (-0.87, 0.48) μm, p=0.012) and rituximab (-0.84 (-1.50, -0.18) μm vs -0.07 ( -1.25, -2.51) μm, p=0.015) in NMOSDON- eyes. Conclusions: This study demonstrated that retinal ganglion cell loss is independent of ON attacks in NMOSD. Tocilizumab and rituximab may delay mGCC thinning in NMOSDON- eyes compared with azathioprine.